DUKUNGAN KELUARGA DAN SOSIAL TERHADAP PENANGGULANGAN HIV/AIDS DI KABUPATEN BANGGAI - MAKU, WAHYU DHARMAWANTO; MOKALU, BENEDICTA; Purwanto, Antonius (JURNAL ADMINISTRASI PUBLIK, 2016)
This study describes the Family Support for PLHA (People Living with HIV/AIDS). The aim of research to obtain data and images of emotional support, Support award, instrumental support, and Support informative. Research conducted using a qualitative approach with descriptive methods. The study design using the technique of case studies with 11 (eleven) informant. Source data used are primary data sources and secondary data sources. Data collection techniques by using in-depth interview, observation and documentation. Mechanical examination of the validity of data by performing persistence observation and triangulation. Analysis of data using qualitative data analysis. The results showed that family support is provided by keluarga consists of four aspects. Emotional support, support awards, support instrumental and informative support given some informants get good enough in the provision of family support. Problems in the can by researchers in the provision of family support persistence of discrimination of PLHA (People Living with HIV/AIDS) families and informants have not the confidence to express to the family. Based on the results of the study concluded that the functioning of the family is very influential in handling people living with HIV, as most people living with HIV have not been confident to express to the family of the already infected HIV positive, then of the people living with HIV do not get support from family.